Paths of grammaticalization of the Lithuanian copula VIRSTI ‘turn into’: The case of the inclusive copular constructions - Mikulskas, Rolandas (Lietuvių kalba, 2019)
In this article I aim to establish source constructions for the inclusive copular construction with the verb virsti ‘turn into’ and to discuss how this once locomotional verb eventually became a copula with an aspectual function in the sentences profiling change events. The research is conducted on the base of data provided by the Dictionary of the Lithuanian Language. As I argued in Mikulskas (2018), the copular construction with this verb along with other copular constructions featuring verbs with similar meaning, such as tapti ‘become’, darytis/pasidaryti ‘become’ (lit. ‘make oneself’) and, formerly, stotis/pastoti ‘become’ (lit. ‘stand up’) express the ingressive aspect of the change event (mainly in the Simple Past and Future tenses). Copular constructions with these verbs may thus be seen as different instantiations of a more abstract ingressive-aspect-expressing construction. While in some contexts these copulas can compete with each other and be used interchangeably, in others their semantic distribution differs. One can reasonably suggest that the copulas under discussion have more or less divided among them the semantic space of aspectual expression according to the semantic and aspectual properties they have inherited from their source constructions. That is why it is so important to trace the source constructions of the copular constructions mentioned above. As is often the case in languages, words retaining their original meanings are still in active usage along with their grammaticalized forms. If this is the case, source constructions are not difficult to detect. The verb virsti (and its prefixed forms) is still widely used in Lithuanian, originally designating the locomotional event of the tumbling down of some vertical object. Thus, locomotional constructions with the verb virsti can be reasonably thought of as the main source of corresponding copular constructions designating a change event. More specifically, the inclusive copular constructions evolved from the locomotional ones through the conceptual metaphor enter a state is moving to a place. Importantly, after a locomotional construction has been reanalysed into a copular one, the latter often preserves formal properties of the former. For example, the starting point of a change event, if expressed in the copular construction with the verb virsti, is coded by the PP [iš NPgen], the same as for the Source participant in the locomotional schema, and the predicative complement of the copular construction after reanalysis often retains the coding of the Goal participant in that schema (i. e. it is coded by PP [į NPacc]). Emerging grammatical construction can benefit not from one but from several sources. In other words, there can be multiple source constructions (Petré 2012). This insight is based on the well-known linguistic fact that the same lexical item, especially a verb, often participates in several different grammatical constructions, and the same construction may attract different verbal lexemes. Copular constructions usually appear in the grammatical context of the locative, existential, possessive or the periphrastic perfect constructions (Mikulskas 2009, 113-141). Technically, this grammatical context surrounding copular constructions may be defined as a network of constructions defined by Ludwig Wittgenstein’s (1958) principle of family resemblance. In the case under discussion, even synchronically, relations of motivation, or asymmetric inheritance links (Goldberg 1995, 72), can easily be posited not only between locomotional constructions with the verb virsti ‘tumble down’ and the corresponding copular constructions, but also between existential constructions with this verb designating events of manifestation, occurrence, befalling and the copular constructions. More specifically, the inheritance links between source constructions and corresponding copular constructions may be defined as various kinds of metaphorical extension. The fact that existential constructions with the verb virsti partake in the formation of inclusive copular constructions with this verb is not accidental, as an existential assertion is always part of any identity statement (Mikulskas 2017, 70-71; Mikulskas 2018, 7). It must also be noticed that existential constructions with the verb virsti are genetically connected to the locomotional constructions with this verb. In fact, certain locomotional events easily acquire an existential interpretation. The crucial point in the evolution of the copular construction under discussion from the two source constructions is the establishment of a so-called subject alternation (Lenartaitė 2011, 129-162) in the domain. This phenomenon can be viewed from two perspectives. First, one may suggest that the schema inherited by the copular construction from its locomotional counterpart becomes a conceptual frame within which there is a space for an existential interpretation of essentially the same scene. In other words, the existential construction and its copular counterpart profile different episodes of the same locomotional schema: in the first construction the Source participant, expressed by the PP [iš + NPGEN]), is focused, but in the second the nominal of this participant is selected as the subject and the subject of the first, existential, construction becomes a part of the copular complement, expressed by the PP [į + NPACC] which formally corresponds to the Goal participant in the schema. From these alternating constructions one can also see that the existential assertion is a part of the more complex statement of identity implying the cognitive operation of comparison in which a newly emerged entity, selected there in the guise of a class representative, in fact plays the role of a standard of comparison. Alternatively, one may suggest that conditions for the alternative subject selection and the ensuing copular construction are formed when the Source participant of the existential construction loses its locational nature and can be interpreted as an individual or a member of some class (which further undergoes transformation into another entity). Finally, the establishment of a subject alternation in existential vs. copular constructions in language may be understood as the actualization of reanalysis (see Barđdal & Gildea 2015, 7 and literature) of the locomotional constructions into copular ones.